Perilaku Konsumtif Memediasi Pengaruh Social Media Marketing dan Fanatisme terhadap Keputusan Pembelian - Fatikha Pramesvara Nugraha; Suharyanto Suharyanto; Chicilia Nova Yatna (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2023)
Purpose The purpose of this research is to analyze the effect of social media marketing and fanaticism on purchasing decisions through consumptive behavior as an intervening variable in purchasing NCT albums. Methodology The population in this study is NCTzens in the Greater Jakarta area. Purposive sampling technique with the characteristics of NCTzens who have bought NCT albums, obtained a total of 100 respondents. Data processing uses the SEM model with SmartPLS version 3.0 software. Findings The results showed that social media marketing and fanaticism had a positive and significant effect on consumptive behavior, social media marketing had a positive and significant effect on purchasing decisions, while fanaticism was not significant on purchasing decisions. Consumptive behavior positively mediates the relationship between social media marketing and fanaticism towards purchasing decisions. Suggestion The fanatical nature of a fan does not necessarily lead to a change in the decision to buy an album. Further research is needed for these two variables.